2022
DOI: 10.1002/mgg3.2020
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations of PMFBP1 in a man with acephalic spermatozoa defects

Abstract: Background: Acephalic spermatozoa (AS) is a serious but rare reproductive genetic disorder that causes infertility in men. To date, only a few genes associated with AS defects have been identified, including the polyamine modulated factor 1 binding protein 1 (PMFBP1) gene. Consistent with this, PMFBP1 localizes to the head-neck connection, which bridges the implantation fossa and basal body.Methods: A male patient was diagnosed as having an AS defect. Blood samples from all family members and a sample of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 29 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…SPATA6 is the first protein identified as a component of the HTCA using the knockout mouse model, and is crucial for the formation of the sperm HTCA (Yuan et al, 2015). Deficiencies in SUN5 (Elkhatib et al, 2017; Fang et al, 2018; Liu et al, 2020; Sha et al, 2018; Shang et al, 2018; Shang et al, 2017; Xiang et al, 2022; Zhang et al, 2021; Zhu et al, 2016) and PMFBP1 (Deng et al, 2022; Liu et al, 2020; Liu et al, 2021; Lu et al, 2021; Nie et al, 2022; Sha et al, 2019; Zhu et al, 2018) have been demonstrated to be associated with ASS in both humans and mice. The centriole-related protein, CENTLEIN, serves as a bona fide linker between SUN5 and PMFBP1 to participates in the HTCA assembly (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…SPATA6 is the first protein identified as a component of the HTCA using the knockout mouse model, and is crucial for the formation of the sperm HTCA (Yuan et al, 2015). Deficiencies in SUN5 (Elkhatib et al, 2017; Fang et al, 2018; Liu et al, 2020; Sha et al, 2018; Shang et al, 2018; Shang et al, 2017; Xiang et al, 2022; Zhang et al, 2021; Zhu et al, 2016) and PMFBP1 (Deng et al, 2022; Liu et al, 2020; Liu et al, 2021; Lu et al, 2021; Nie et al, 2022; Sha et al, 2019; Zhu et al, 2018) have been demonstrated to be associated with ASS in both humans and mice. The centriole-related protein, CENTLEIN, serves as a bona fide linker between SUN5 and PMFBP1 to participates in the HTCA assembly (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%